Risk-taking behavior and internet addiction from gender perspective - Ladikli, Nefise; Ziyalar, Neylan (Journal of Dependence, 2021)
Objective: This research aims to examine risk-taking behaviors and internet usage within the context of gender, to reveal possible connections between internet addiction and risk-taking behaviors in certain areas of daily life.Method: 539 participants, 260 (48.2%) female and 279 (51.8%) male, participated in the study. Participants were administered a sociodemographic form, a Domain-Specific Risk Attitude Scale (DOSPERT) to examine risk-taking behaviors and Internet Addiction Scale (IAS) to evaluate level of internet addiction.Results: There was a statistically significant difference between mean rank scores of men's and women's risk-taking behaviors. It was observed that, men had high mean score in ethics in everyday life, gambling and security, and women had high mean score in social sub-dimension. There was no significant difference between the mean scores of IAS. A positive correlation was found between IAS and whole sub-domains of DOSPERT. In order to determine the effect of gender in this correlation, the dataset splitted by gender groups were analyzed and a significant correlation was found between the sum of women’s and men’s IAS and DOSPERT domain scores.Conclusion: The average internet users has lower averages in all areas of risk taking behavior than internet addicts and individuals at risk of internet addiction.
Keywords: Risk-taking behavior; addiction; attitude to computers; health risk behaviors